Operating list composition and surgical performance. Issue 8 (20th March 2018) - Pike, T. W.; Mushtaq, F.; Mann, R. P.; Chambers, P.; Hall, G.; Tomlinson, J. E.; Mir, R.; Wilkie, R. M.; Mon‐Williams, M.; Lodge, J. P. A.
Abstract : Background: Recent reviews suggest that the way in which surgeons prepare for a procedure (warm up) can affect performance. Operating lists present a natural experiment to explore this phenomenon. The aim was to use a routinely collected large data set on surgical procedures to understand the relationship between case list order and operative performance. Method: Theatre lists involving the 35 procedures performed most frequently by senior surgeons across 38 private hospitals in the UK over 26 months were examined. A linear mixed‐effects model and matched analysis were used to estimate the impact of list order and the cost of switching between procedures on a list while controlling for key prognosticators. The influence of procedure method (open versus minimally invasive) and complexity was also explored. Results: The linear mixed‐effects model included 255 757 procedures, and the matched analysis 48 632 pairs of procedures. Repeating the same procedure in a list resulted in an overall time saving of 0·98 per cent for each increase in list position. Switching between procedures increased the duration by an average of 6·48 per cent. The overall reduction in operating time from completing the second procedure straight after the first was 6·18 per cent. This pattern of results was consistent across procedure method and complexity. Conclusion: There is a robust relationship between operating list composition and surgical performance (indexed by duration of operation). An evidence‐based approach to structuring a theatre list could reduce the total operating time. Abstract : Science behind list structure